Raiding of agricultural crops and forests by wild boar (Sus scrofa L.) and its mitigation tricks - Sarwar, Muhammad (Journal of Scientific Agriculture, 2019)
Wild boar (Sus scrofa L.), is the utmost communal native species of wildlife to bring about plants injury. In this article, it is proved that wild boar is an important factor and a particular concern to the agricultural industry regarding crops and frosts damage along with its alleviating tactics. Wild boar may destroy to agricultural crops by crushing or eating of plants. Likewise, these may harm to crops while wallowing and rooting which injury to plant roots, and form holes and grooves that harm farm equipment and endanger operations. Wild boar injury is more in fields that are in neighboring vicinity of forests ranges. Wild boars harshly influence trees and timber resources in many ways like disturbance of planted seedlings, girdling and rubbing of matured trees, chewing and rooting of sideway roots of fully-fledged trees, and tusking or scent marking with the tusk glands that injuries to tree bark. Mitigation strategies for wild boar losses comprise creation of education and awareness among persons, co-operative securing of matured crops and use of local protective methods. Wild boar can be managed through small-scale exclusion, trapping and shooting tactics. Shooting is a popular method of controlling wild boar populations and in this way pressure from hunting will let the pest to move away from where they are hunted, or at a minimum, will restrict their movements. It has been found that using of dogs is the most effective for locating of individuals or smaller groups of wild boars. In some cases, a female boar is trapped, spayed fitted with a radio collar and then released in field. Since female boars live in groups, the spayed female will lead wildlife managers to local boar populations, which can assist in population control efforts. While recreational hunting is often a preferred method, it is also effective to some extent at controlling of wild boar population growth. Trapping, however, is highly effective at controlling and reducing of boar’s population growth. The study of spatiotemporal variant of boar-inflicted losses and recognition of reasons which boost the risk of harm delivers necessary facts for contributing to develop a further effectual strategy for handling of wild boar’s density.